Micro-nano zinc nitrate hexahydrate film fabricated by biomimetic mineralization - Lu, F.; Meng, F.F.; Wang, L.L.; Dai, Y.Q. (Functional Materials, 2019)
In this work, Zn(NO₃)₂·6H₂O micro-nano rods are successfully fabricated by a biomimetic mineralization process. During synthetic process, the self-assembly monolayers with different terminal groups are used as templates to induce the nucleation and growth of Zn(NO₃)₂·6H₂O crystals. The products obtained at different conditions are characterized by means of X-ray diffraction patterns, scanning electron microscopy. The results show that the orientation and morphology of the Zn(NO₃)₂·6H₂O crystals are controlled properly by tuning the terminal groups of the self-assembled monolayers.